2017
DOI: 10.1371/journal.pone.0184638
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microclimatic variables on the symptoms and signs onset of Moniliophthora roreri, causal agent of Moniliophthora pod rot in cacao

Abstract: Moniliophthora Pod Rot (MPR) caused by the fungus Moniliophthora roreri (Cif.) Evans et al., is one of the main limiting factors of cocoa production in Latin America. Currently insufficient information on the biology and epidemiology of the pathogen limits the development of efficient management options to control MPR. This research aims to elucidate MPR development through the following daily microclimatic variables: minimum and maximum temperatures, wetness frequency, average temperature and relative humidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 27 publications
0
16
0
4
Order By: Relevance
“…En zonas con promedio de lluvias de 1000 a 1200 mm durante los tres meses del año más calientes, las probabilidades de ocurrencia de Mr son mayores, lo cual también estaría relacionado con los tiempos en los cuales se inicia un nuevo ciclo de infección secundaria. En la fase biótrofa del hongo, la espora requiere frecuencias de humedad relativas altas para germinar, principalmente durante los primeros estadios de crecimiento de los frutos jóvenes del cacao (chireles o pepinos) o mazorcas en desarrollo (entre los 0 y 10 cm de longitud) (Leandro-Muñoz et al, 2017).…”
Section: Discussionunclassified
See 3 more Smart Citations
“…En zonas con promedio de lluvias de 1000 a 1200 mm durante los tres meses del año más calientes, las probabilidades de ocurrencia de Mr son mayores, lo cual también estaría relacionado con los tiempos en los cuales se inicia un nuevo ciclo de infección secundaria. En la fase biótrofa del hongo, la espora requiere frecuencias de humedad relativas altas para germinar, principalmente durante los primeros estadios de crecimiento de los frutos jóvenes del cacao (chireles o pepinos) o mazorcas en desarrollo (entre los 0 y 10 cm de longitud) (Leandro-Muñoz et al, 2017).…”
Section: Discussionunclassified
“…Un mayor porcentaje de isotermia (aprox. 100 %) puede influir positivamente en la probabilidad de presencia (0,8) de Mr. La isotermia es una medida de las condiciones de temperatura estables y homogéneas durante los meses del año de una región, y esta variable podría influir en la fase intermedia biotrófica del hongo e inicial de la necrotrófica, en las cuales el hongo necesita una temperatura relativamente constante durante el crecimiento micelial en el interior del fruto y su posterior proceso de esporulación externa (Leandro-Muñoz et al, 2017).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…M. roreri has an extensive incubation and latency period (40 to 60 days). Warm temperatures (20 to 27 °C) and high relative humidity (80 to 100%) are appropriate environments for the germination of its spores and the fast fungal penetration [ 44 ]. Leandro-Muñoz et al [ 44 ], applying statistical and mathematical modelling to determine the relationship between environmental conditions and Moniliophthora pod rot development, found that the fungal microclimatic requirements vary throughout the cycle, probably because M. roreri has a long latent period.…”
Section: Preharvestmentioning
confidence: 99%